Social Mobility: Charting the Economic Topography of Urban Space. (May 2017) - Zwicker, Heather; Supernant, Kisha; Luckert, Erika
This project on economic topographies is one of eight thematic ways in which the research group Edmonton Pipelines is remapping the neighborhood of Rossdale. The essay brings together poetry, data visualization, and technologies of mapping to analyze how the twin vectors of capitalism and colonialism have created Western Canadian cityspace. Rather than taking for granted the ups and downs of the built environment, the article muses on the possibilities of using haunting as an urban interface. Working through this metaphorical possibility concretely, this essay traces the contours of haunting in the case of Rossdale, a Canadian neighborhood that has undergone an emblematic form of gentrification. We develop literal topographical maps as a way of conceptualizing metaphorical hurdles to belonging to settler colonial cities. These socioeconomic topographical maps serve as a new form of urban cartography.